Why do mothers die? A retrospective analysis of maternal mortality over 7 years in a tertiary care teaching Hospital in North Karnataka, India - Yaliwal, Rajasri G.; Biradar, Aruna M.; Kori, Shreedevi S.; Mudanur, SUbhashchandra R.; Pujeri, Shivakumar U.; Sushmita, Jada (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Maternal mortality ratio (MMR) is still high in many developing countries. In Southern India, the maternal mortality is highest in the state of Karnataka. Therefore, a study was conducted at BLDE (DU) Shri BM Patil medical college, hospital and research centre to study the causes of maternal deaths, and to make recommendation to reduce the maternal mortality. Methods: A retrospective analysis of all the maternal deaths between 2012 to 2019 was done. Results: A total of 58 women died due to pregnancy and its complications during the period of 2012-2019. Average age of death was 25.42 years. It was noted that 70.7% of the patients travelled over 30 km to reach Vijayapura city. The predisposing causes of death were post-partum haemorrhage (44.8%) eclampsia (18.9%), anaemia (17.2%), pulmonary or amniotic fluid embolism (12.1%), sepsis (10.3%) antepartum haemorrhage (3.4%) and cardiac disease (6.9%). A death each occurred in patients suffering cholestasis and adult respiratory distress syndrome. A majority of the deaths were post-partum deaths (84%). Most of the deaths of the occurred during the first 12 hours of admission (82.76). A total of 11 patients received blood and blood components. Of the 58 deaths, 56(96%) required ventilatory support., 47 (81%) patients received ionotropic support. 11 (19%) patients underwent peripartum hysterectomy. Conclusions: Timely intervention can save maternal lives. Services of well-equipped hospitals with obstetric intensive care units having a dedicated team of well-trained obstetricians, intensivists and anaesthesiologist are recommended in a facility which is near the residence of the pregnant women. Facilities for quick transfer of the cases who are high risk are required.